Is ischemic modified albumin a marker in osteomyelitis patients? - Cihan Adanas; Sezai Ozkan; Canan Demir (Journal of the Pakistan Medical Association, 2020)
Objective: To compare the levels of ischemia modified albumin between osteomyelitis patients and healthy controls. Method: The cross-sectional prospective study was conducted at Van Yüzüncü Y?l University, Van, Turkey, from May 2018 to May 2019, and comprised inpatients diagnosed with osteomyelitis, and healthy controls. Serum IMA concentrations were determined spectrophotometrically at 470nm wavelength. Serum ischemia modified albumin levels were measured and compared between the patients and the controls. Data was analysed using SPSS 20. Results: Of the 77 subjects, 37(48%) were patients and 40(52%) were controls. Serum ischemia modified albumin level in patients was significantly higher than controls (p<0.05). There was a significant correlation between ischemia modified albumin and C-reactive protein levels (p<0.05). Conclusion: Serum ischemia modified albumin level in patients was significantly higher than controls (p<0.05). Key Words: Osteomiyelitis, Ischemia-modified albumin, Receiving operation curve, Biomarker, C-reactive protein. Continuous...